BNF 70 : Murtadha Alshareifi. - Alshareifi, Murtadha (London : BMA, 2016)
The British National Formulary (BNF) is your essential reference book for prescribing, dispensing, and administering medicines.
Keywords: Pharmaceutical; Medicine -- Formulae; Receipts; Prescriptions; MEDICAL -- Pharmacology; Pharmacopoeias -- Great Britain